Hubungan Kualitas Tidur, Aktivitas Fisik, dan Tingkat Konsumsi Zat Gizi Makro dengan Gizi Lebih pada Mahasiswa Universitas Airlangga Angkatan 2019 - Hasanah Ayuningtyas; Siti Rahayu Nadhiroh (Universitas Airlangga, 2023)
Background: Overweight is a global health problem caused by many factors. Poor sleep quality can be at risk of eating at night due to an imbalance of appetite-regulating hormones. The absence of physical activity carried out after such a dinner is risk of increasing body weight. In addition, poor consumption habits, such as high in energy, high in fat, high in simple carbohydrates, and low in fiber, which are often done by students, can cause excess weight. Objective: To analyze the relationship between sleep quality, physical activity, and level consumption of macronutrients with overweight in 2019 Universitas Airlangga students. Methods: This research used cross sectional design. The sample was 107 students selected from proportionate stratified random sampling from 13 faculties. Data collection included interviews and online questionnaires about individual characteristics, breakfast habits, PSQI, IPAQ-SF, and food recall 2x24 hours. Meanwhile, the statistical analysis used is the chi-square test. Results: There was a correlation between physical activity (p=0.018), energy consumption level (p=0.009), protein consumption level (p=0.000), and fat consumption level (p=0.000) with overweight in Universitas Airlangga student class of 2019. Conclusion: It can be concluded that there was a correlation between physical activity, level of energy consumption, level of protein consumption, and level of fat consumption with overweight. This was due to the density of student activities and the lack of awareness of a healthy lifestyle among students. Recommendations given by students are to increase knowledge and awareness related to healthy living behavior to prevent malnutrition.